The Observer Observed. The Promise of the Posthuman: Homeostasis, Autopoiesis and Virtuality in Samuel Beckett. Issue 2 (September 2018) - Vos, Laurens De
Abstract : This essay will argue that the structure and poetics of many Beckett plays follows the technological and informational new, self-generative patterns that have been associated with posthumanism. If we can distinguish three main waves in posthumanism – homeostasis, reflexivity and virtuality –, it appears that these can be clearly discerned in Beckett's work. Drawing on examples from among others Krapp's Last Tape, Endgame, Play and Ohio Impromptu, we will not only trace this posthumanist inclination, but align this way of thinking to the wave of performativity that emerged in the second half of the 20 th century. Thus, Beckett also informs us about the underlying ideology of posthumanism itself.